2021
DOI: 10.3390/toxins13080540
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Ochratoxin A in Different Types of Cheese Offered for Sale in Italy

Abstract: The detection of Ochratoxin A (OTA) in the milk of ruminants occurs infrequently and at low levels, but its occurrence may be higher in dairy products such as cheese. The aim of this study was to investigate the presence of OTA in cheeses purchased in the metropolitan city of Bologna (Italy) and the surrounding area. For the analysis, a LC-MS/MS method with a limit of quantification (LOQ) of 1 µg/kg was used. OTA was detected in seven out of 51 samples of grated hard cheese (concentration range 1.3–22.4 µg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 66 publications
(87 reference statements)
2
18
0
Order By: Relevance
“…In three samples (10%), which belonged to the category of grated hard cheeses, the concentration of the mycotoxin was above our LOQ (1 µg/kg) with levels of 1.14, 1.52, and 4.7 µg/kg; in another case, it was lower than LOQ. Data collected are in agreement with those reported in the recent study conducted by Altafini et al (2021), in which seven out of the 84 different types of cheeses analyzed, with OTA values ranging between 1.3 and 22.4 µg/kg, were grated hard cheeses. Moreover, Biancardi et al (2013), in six out of 40 commercially grated cheeses analyzed, detected OTA at concentrations ranging from 1.62 to 54.07 µg/kg.…”
Section: Cheese Samplessupporting
confidence: 91%
“…In three samples (10%), which belonged to the category of grated hard cheeses, the concentration of the mycotoxin was above our LOQ (1 µg/kg) with levels of 1.14, 1.52, and 4.7 µg/kg; in another case, it was lower than LOQ. Data collected are in agreement with those reported in the recent study conducted by Altafini et al (2021), in which seven out of the 84 different types of cheeses analyzed, with OTA values ranging between 1.3 and 22.4 µg/kg, were grated hard cheeses. Moreover, Biancardi et al (2013), in six out of 40 commercially grated cheeses analyzed, detected OTA at concentrations ranging from 1.62 to 54.07 µg/kg.…”
Section: Cheese Samplessupporting
confidence: 91%
“…The EU fixed specific limits for OTA in some foodstuffs (dairy products excluded), and considering the OTA limits set for cereals, dried vine fruits and spices (3, 10 and 15 µg kg −1 , respectively), the percentages of grated cheese samples exceeding these values were 20%, 5% and 3%, respectively. OTA occurrence in grated cheeses has been recently reported by Altafini et al [ 15 ] in 7 out of 51 samples of grated hard cheese, with concentrations ranging between <LOD and 22.4 µg kg −1 . A similar incidence was previously reported by Biancardi et al [ 14 ], where OTA was detected in 15% of grated cheese samples collected from retail shops in Northern Italy, with a contamination level ranging between <LOD and 54.07 μg kg −1 .…”
Section: Discussionmentioning
confidence: 84%
“…This first survey, performed on 40 grated cheese products, showed that 15% of the samples were contaminated by OTA. More recently, Altafini et al [ 15 ] showed a similar rate of OTA contamination in grated cheeses collected in the urban area of Bologna (Italy). Unfortunately, to our knowledge, no data on the occurrence of STC in grated cheese products is available so far, even if its presence has already been reported in ripened cheeses [ 16 ].…”
Section: Introductionmentioning
confidence: 89%
“…Compared with our results, all are below our maximum detection. Although there are no regulations in other countries of the European Union for OTA in milk, Slovakia sets a limit of 5 µg/kg for milk [ 42 ]. Thus, 25.81% of the samples exceeded the Slovak limit for OTA in milk.…”
Section: Discussionmentioning
confidence: 99%